Global update on the susceptibility of human influenza viruses to neuraminidase inhibitors and status of novel antivirals, 2016–2017 - Lackenby, Angie; Besselaar, Terry G.; Daniels, Rod S.; Fry, Alicia; Gregory, Vicki; Gubareva, Larisa V.; Huang, Weijuan; Hurt, Aeron C.; Leang, Sook-Kwan; Lee, Raphael T.C.; Lo, Janice; Lollis, Lori; et al. (Antiviral research, 2018)
A total of 13672 viruses, collected by World Health Organization recognised National Influenza Centres between May 2016 and May 2017, were assessed for neuraminidase inhibitor susceptibility by four WHO Collaborating Centres for Reference and Research on Influenza and one WHO Collaborating Centre for the Surveillance Epidemiology and Control of Influenza. The 50% inhibitory concentration (IC50) was determined for oseltamivir and zanamivir for all viruses, and for peramivir and laninamivir in a subset (n = 8457). Of the viruses tested, 94% were obtained from the Western Pacific, Americas and European WHO regions, while limited viruses were available from the Eastern Mediterranean, African and South East Asian regions. Reduced inhibition (RI) by one or more neuraminidase inhibitor was exhibited by 0.2% of viruses tested (n = 32). The frequency of viruses with RI has remained low since this global analysis began (2015/16: 0.8%, 2014/15: 0.5%; 2013/14: 1.9%; 2012/13: 0.6%) but 2016/17 has the lowest frequency observed to date. Analysis of 13581 neuraminidase sequences retrieved from public databases, of which 5243 sequences were from viruses not included in the phenotypic analyses, identified 58 further viruses (29 without phenotypic analyses) with amino acid substitutions associated with RI by at least one neuraminidase inhibitor. Bringing the total proportion to 0.5% (90/18915). This 2016/17 analysis demonstrates that neuraminidase inhibitors remain suitable for treatment and prophylaxis of influenza virus infections, but continued monitoring is important. An expansion of surveillance testing is paramount since several novel influenza antivirals are in late stage clinical trials with some resistance already having been identified. •A total of 13,672 influenza viruses were collected worldwide, May 2016–May 2017.•Approximately 0.2% showed reduced inhibition by at least one NA inhibitor.•The frequency of viruses with reduced inhibition by NA inhibitors was at the lowest since analysis began in 2012.•Newly licenced antivirals and drugs currently in clinical trials are summarized.•Global surveillance of influenza antiviral susceptibility should be continued.